2023
DOI: 10.3390/agriculture13061261
|View full text |Cite
|
Sign up to set email alerts
|

Response of New Yellow Lupin Varieties to Inoculation with Bradyrhizobium sp. Lupinus under Central European Conditions

Abstract: The aim of a two-factorial field experiment was to determine how the inoculation of seeds/soil with preparations of Bradyrhizobium sp. Lupinus (Nitragina—seed inoculation, Nitroflora I—seed inoculation, Nitroflora II—soil inoculation, HiStick® Lupin—seed inoculation) affected plant development, seed chemical composition and yield of two yellow lupin varieties (Bursztyn, Puma). This experiment was carried out with four replications in 2018 and 2019 in Poland. Precipitation during both vegetation periods was sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…The highest protein content (38.5%) was obtained in 2016, while the lowest was in 2019 (32,3%). The difference in protein content and yield in lupin seeds depends on the temperature, sum, and distribution of precipitation during the growing season, which was found in yellow lupin [10], but also in peas [40] and other Fabaceae species [46,47]. In a study conducted by Prusinski and Borowska [40] on peas, weather conditions also had an effect on seed protein content.…”
Section: Protein Yield and Protein Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest protein content (38.5%) was obtained in 2016, while the lowest was in 2019 (32,3%). The difference in protein content and yield in lupin seeds depends on the temperature, sum, and distribution of precipitation during the growing season, which was found in yellow lupin [10], but also in peas [40] and other Fabaceae species [46,47]. In a study conducted by Prusinski and Borowska [40] on peas, weather conditions also had an effect on seed protein content.…”
Section: Protein Yield and Protein Contentmentioning
confidence: 99%
“…Lupine, in addition, improves soil structure [3] and can be used for cultivation in various agricultural systems [9]. White lupin is grown for seed, ruminant feed, green manure, and for human nutrition [10,11]. Erbas et al [12] showed that white lupin grown in Turkey is an excellent food commodity with high nutritional value.…”
Section: Introductionmentioning
confidence: 99%